Identification of pigmented-fleshed potato clones of high marketable yield and better frying quality: Stability and multivariate analysis of genotype-environment interaction - Tirado-Lara, Roberto (2020)
In the present research, nineteen advanced potato clones with pigmented-fleshed were analyzed in two potato-producing localities in Cajamarca, Peru, during two agricultural seasons, by means of the combined analysis of variance, the model of additive main effects and multiplicative interaction (AMMI) and the Biplot analysis, to analyze the genotype-environment interaction (GEI), in order to select clones with high stability of marketable yield and quality. Multivariate analysis showed differences for the main effects of genotypes, environments and GEI. Which states that the genetic makeup of each clone and the environment influenced the marketable yield and frying color due to the polygenic character that governs these characteristics. The results identified the CIP clone 302299.28 with red and cream fleshed and red skin with low IGA, which indicates that it is a stable clone with high commercial yield with 31.8 t ha-1 and a scale of 2 in the frying color, obtaining a better response to environmental variation. Followed by CIP clone 302281.17 with fleshed and yellow skin, which showed commercial yield stability with 32 t ha-1 and 2.2 of frying color. Likewise, CIP clone 302280.23 of fleshed and violet skin reported a marketable yield of 33.0 t ha-1, and 1.7 on the frying color scale, obtaining quality stability, being a clone for the processing industry in strips, flakes and other derivatives. Therefore, these clones are selected for wide production in Cajamarca.